(untitled) (Research, Society and Development, 2023)
For critically ill patients, drug prophylaxis of acute gastric mucosal injury can be defined as the prevention or reduction in gastrointestinal bleeding rates by the use of drugs. The aim of this study was to gather scientific evidence on drug prophylaxis of acute gastric mucosal injury for the development of an institutional protocol for critically ill patients. This is a literature review based on the elaboration of a guiding question for the research, using the acronym PICO. The databases used to search for articles were PubMed, Lilacs and Cochrane, in addition to the gray literature. 98 articles were found, 78 in PubMed, 19 in Lilacs and 01 in Cochrane. After selection strategies, 13 studies were included, which were read in full for the construction of the protocol. Study bias was assessed according to the JADAD scale. It is possible to conclude that there is evidence supporting the use of drug prophylaxis for acute gastric mucosal injury in critically ill patients with known risk factors. Other measures can also help prevent stress ulcers, and their indication should be periodically reassessed.